Contribuição ao estudo do genêro Tmarus Simon, 1875, no Brasil (Araneae, Thomisidae) - Garcia Neto, Lucia Nascimento (1981)
A study is made of the species of Tmarus Simon, 1875 occuring in Brazil from the point of view of systematics, analizing the data in the literature as well as the material in the collections of the following institutions: Museu Nacional, da Universidade Federal do Rio de Janeiro; Museu de Zoologia da Universidade de São Paulo; Museu de Zoologia da Escola Superior de Agricultura Luiz de Queiroz de Piracicaba; Museum National d' Histoire Naturelle de Paris; Fundação Zoobotânica do Rio Grande do Sul. The localities of occurence of the genus were related to the 1 : 1000000 map of Brazil. Twenty nine plates are also given one of them being a map of the occurences of the genus in Brazil and the other containing eighty seven figures.